Efeito de fertilizantes mineral, organomineral e orgânico sobre a macrofauna e mesofauna do solo. - Krolow, Ivan Renato Cardoso (2011)
The study was performed on a rural property in the locality the Hidraulica city of Capão do Leão - Rio Grande do Sul, Brazil, to evaluate the influence of mineral fertilizers, organo-mineral and organic on macrofauna and mesofauna the soil. We used the following succession crops: Zea mays L.-forage Consortium (Trifolium repens L., Trifolium pratense L., Lotus corniculatus L. and Lolium multiflorum Lam), Sorghum bicolor L., Brassica napus L., Panicum maximum-Lolium multiflorum Lam, Helianthus annuus L.-Triticum aestivum L. Investigated the following treatments: T1-Control, T2-fertilizer mineral , T3- organo-mineral fertilizer, T4-compost fertilizer and T5-organic fertilizer turkey litter. The variables were: precipitation, soil properties (pHágua, pHSMP, electrical conductivity, organic carbon, nitrogen, carbon / nitrogen, phosphorus, potassium, calcium, magnesium, iron, aluminum, sodium, manganese, copper and zinc), attributes Soil physical (moisture and temperature), agronomic responses (yield and biomass) and soil macrofauna and mesofauna. Sowing of summer species occurred in December 2007, while those of winter, in May 2008. Grain crops were harvested at the end of their cycle, while forage in summer and winter amounted to seven six cuts successive, respectively. The results of soil temperature, soil moisture, yield, agronomic and representatives of the fauna were subjected to analysis of variance, mean test (Duncan 5%) probability. The fauna found was also analyzed for density, richness, relative frequency, classification by Abundance, diversity index and evenness index. Results related to soil fauna, macronutrients, micronutrients and soil conductivity were also submitted to multivariate analysis. The Fertilizers compost and organic-mineral was associated more effectively the majority of taxos, justifying larger the variation of data the exception of the catch of the soil inner in the culture of aruana. In experiment 1 the groups Acari, Lepidoptera, Diptera, Coleoptera, Oligochaeta and Nematoda and nitrogen content, zinc, magnesium, manganese, phosphorus and calcium were those who 9 had contributed more in variation of the data. In experiment 2 the groups Isopoda, Diplura, Myriapoda, Acari and Dermaptera and the magnesium, nitrogen, phosphorus, zinc, copper, sodium, aluminum and iron were those who had contributed more in variation of the data. In experiment 3 the groups Lepidoptera, Hymenoptera, Diplura, Myriapoda, Protura and the magnesium, nitrogen, iron and manganese were those who had contributed more in variation of the data. In experiment 4 the groups Acari, Nematoda, Dermaptera, Protura, Diplura, Coleoptera and Oligochaeta and the contents of potassium, iron, copper and calcium were those who had contributed more in variation of the data.